Preliminary Experience with Yttrium-90-labelled Rituximab (Chimeric Anti CD-20 Antibody) in Patients with Relapsed and Refractory B Cell Non-Hodgkins Lymphoma - Thakral, Parul; Singla, Suhas; Vashist, Atul; P. Yadav, Madhav; K. Gupta, Santosh; S. Tyagi, Jaya; Sharma, Atul; S. Bal, Chandra; Snehlata; Malhotra, Arun (Current Radiopharmaceuticals, 2016)
Background and Objectives: The aim of the study is to evaluate the therapeutic efficacy and safety of Yttrium- 90 radiolabelled chimeric anti CD20 antibody-Rituximab in the treatment of patients with relapsed/ refractory B cell Non-Hodgkins Lymphoma (NHL). Methods: Twenty patients with relapsed/refractory CD20+ NHL in progressive state were included in the study. These patients had undergone a median of 2 (range 2-5) prior standard chemotherapy ± immunotherapy regimens. All the patients received rituximab 250 mg/m2 on days 1 and 8, and either 14 MBq/kg (0.4 mCi/kg) or 11 MBq/kg (0.3 mCi/kg) of Y-90 Rituximab on day 8 (maximum dose, 32 mCi) depending upon their platelet count. The patients were observed for systemic toxicity and response for at least 12 weeks after therapy. Results: No acute adverse effects were observed after the administration of 90Y-Rituximab. Overall response rate (ORR) was 45% of which complete response (CR) was observed in 2 patients, stable disease in 1 patient and partial response in 6 patients. The therapy was well tolerated with grade IV thrombocytopenia, neutropenia and anemia observed in 3, 4 and 2 patients respectively. Conclusion: 90Y-Rituximab therapy is safe and well tolerated in high risk extensively pretreated NHL patients. Toxicity is primarily hematologic, transient and reversible.
Keywords: FDG PET